PENGARUH PEMBELAJARAN LITERASI SAINS TERHADAP KEMAMPUAN BERPIKIR LOGIS PADA KELOMPOK B DI TK PLUS AL HIKMAH - Aryani Sri Handayani; Sharina Munggaraning Westhisi (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2021)
The purpose of this study was to describe the effect of scientific literacy learning on logical thinking skills in group b at TK Plus Al Hikmah. The research method used is descriptive quantitative. The subjects of this study were the class teachers and students of group B TK Plus Al Hikmah, totaling 23 students. The data sources in this study were informants consisting of managers, educators, and students at TK Plus Al Hikmah. Sources of data were also obtained from annual programs until daily programs, data obtained from TK Plus Al Hikmah when researchers conducted interviews and field observations. Data collection techniques using observation, interviews, and documentation. The results of the study were 1) scenarios and implementation of science literacy learning, 2) the response of group B kindergarten teachers and students to science literacy learning, and 3) the obstacles experienced by group B kindergarten children in participating in science literacy learning. The results of this study have reached the expected indicators, using scientific literacy learning can improve the logical thinking skills of early childhood.